Dinâmicas de uma instituição total e carreira moral: famílias, equipe médica e “doentes mentais” no Hospital Nina Rodrigues em São Luis – MA - NASCIMENTO, Emanuelle do Espírito Santo Alves do (2020)
The paper aims to explain how transformations and institutional dynamics can contribute to produce certain moral careers of social actors generically classified as "mentally ill". The empirical field was defined as the Nina Rodrigues Psychiatric Hospital in São Luís-MA, taken here as a “Total Institution”, according to Erving Goffman's classic concept. It is the first and only public psychiatric hospital in the State built in 1941 and which over the years has undergone several institutional transformations. This analysis is in the context of a sociology of interactions that promotes mastery of face-to-face interactions or microanalysis, termed “order of interaction” as analytically viable (Goffman). After a review of the specific literature on these analytical categories, the work puts in perspective the socio-history of psychiatric institutions in Brazil and, specifically, in Maranhão. And develops an ethnographic description of the physical spaces of the Hospital and the dynamics in the process of hospitalization of patients classified as "mentally ill". The empirical data were constructed from direct observation accompanied by interviews with medical staff, patients, family members, technical staff and management. The study reveals that the order of interaction between institutional actors, families and patients implies the production of certain careers for those classified as “mentally ill”.